2020
DOI: 10.12688/f1000research.22700.1
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibitor, captopril, attenuates cytopathic effects of herpes simplex virus 1 in SH-SY5Y cells

Abstract: Background: Over 60% of the United States population is infected with herpes simplex virus 1 (HSV-1). Current HSV-1 treatment regimens exert their antiviral effects through a common mechanism of action and suffer from high dosing frequencies, which may contribute to patient noncompliance and the subsequent development of antiviral resistance. Although primarily known for their functions in maintaining homeostatic control of arterial blood and osmotic pressures, components of the Renin-Angiotensin Aldosterone S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, reducing the concentration of angiotensin-2 by suppressing ACE in the body is important for preventing and/or supporting the treatment of cardiovascular events [7]. Also, most strikingly, some studies have recently reported the antiviral effect of ACE inhibitors [9,10]. Various studies have investigated the effectiveness of these inhibitors for the SARS-CoV-2 virus (Severe Acute Respiratory Syndrome-Coronavirus 2) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing the concentration of angiotensin-2 by suppressing ACE in the body is important for preventing and/or supporting the treatment of cardiovascular events [7]. Also, most strikingly, some studies have recently reported the antiviral effect of ACE inhibitors [9,10]. Various studies have investigated the effectiveness of these inhibitors for the SARS-CoV-2 virus (Severe Acute Respiratory Syndrome-Coronavirus 2) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing the concentration of angiotensin-2 by suppressing ACE in the body is quite important for preventing and/or supporting the treatment of cardiovascular events (Georgalaki et al 2007). Also, most strikingly, some studies have recently reported the antiviral effect of ACE enzyme inhibitors (Wofford et al 2020;Kuhn Hadizadeh, 2021). Various studies have been investigating the effectiveness of these inhibitors for the SARS-CoV-2 virus (Kuhn Hadizadeh, 2021).…”
mentioning
confidence: 99%